Behaviors associated with mobbing in adolescent relationships / Comportamente asociate mobbing-ului în relațiile dintre adolescenți - BICAN Ovidiu (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The objective of the research presented in this article is to measure the incidence of different types of behaviors associated with mobbing in the relationships between teenagers. The main results reveal that the vast majority of teenagers surveyed declare a high presence of mobbing in their schools. According to the answers, in most cases, the bullies are the groups of boys who come from the same class or group of friends as the victim. When they are bullied, the majority of teenagers first try to resolve the conflict peacefully. Those who find out about the incident are mainly the colleagues of the victims, and they are also the ones who offer support to colleagues who are subjected to aggression. Regarding the research hypotheses, we noticed that there are differences between boys and girls regarding the status of being a victim of mobbing, but only for the physical forms.